The Politics of Intellectual Property Rights and Access to Medicines - Muzaka, Valbona. author. aut Link
IX, 181 p.
Keywords: This book shows why contests over intellectual property rights and access to affordable medicines emerged in the 1990s and how they have been 'resolved' so far. It argues that the current arrangement mainly ensures wealth for some rather than health for all, and points to broader concerns related to governing intellectual property solely as capital.